On South African Violence Through Giorgio Agamben’s Biopolitical Framework: A Comparative Study Of J.M. Coetzee’s Disgrace And Z. Mda’s Ways Of Dying - Bartnik, Ryszard (Studia Anglica Posnaniensia, 2015)
In this article I argue that the developments of countries going through transition from authoritarian to democratic rule are always stamped by numerous references to formerly sanctioned and fully operational institutionalized violence. A perfect exemplification of this phenomenon is [post-] apartheid South Africa and its writing. In the context of the above, both the social and the literary realm of the 1990s might be perceived as resonant with Giorgio Agamben’s ‘concentrationary’, deeply divisive imaginary. Escaping from, and concurrently remembering, past fears, anxieties, yet seeking hope and consolation, the innocent but also the formerly outlawed and victimized along [interestingly enough] with [ex]perpetrators exemplify, as discussed in J. M. Coetzee’s and Z. Mda’s novels, the necessity of an exposure of the mechanism of South African ‘biopoliticization’ of life. Their stories prove how difficult the uprooting of the mentality of segregation, hatred and the policy of bracketing the other’s life as insubstantial, thus vulnerable to instrumental violence, in [post-] apartheid society was. In view of the above what is to be highlighted here is the authorial perception of various attempts at disavowing past and present violence as detrimental to South African habitat. In the end, coming to terms with the past, with the belligerent nature of local mental maps, must inevitably lead to the acknowledgement of guilt and traumatic suffering. Individual and collective amnesia conditioned by deeply-entrenched personal culpability or personal anguish is then construed as damaging, and as such is subject do deconstructive analysis.